2021
DOI: 10.3390/nursrep11030052
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Facilitation of Interprofessional Education Programs: An Institutional Ethnography

Abstract: Interprofessional collaboration (IPC) among health care professionals has been identified as essential to enhance patient care. Interprofessional education (IPE) is a key strategy towards promoting IPC. Several factors including the nature of facilitation shape the IPE experience and outcomes for students. Stereotypes held by students have been recognized as a challenge for IPE and IPC. This study aimed to explore institutional rules and regulations that shape facilitators’ work in IPE interactions problematiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In this way, we create diverse interprofessional student teams that can explore and learn about the roles and responsibilities of other team members while they work on the development and practice of effective communication with each other and their community participants. This method of promoting IPE is consistent with Ezzendine and Price, who found that forming student teams, facilitating student introductions, and facilitating team dynamics were valuable [ 15 ].…”
Section: Methodssupporting
confidence: 77%
“…In this way, we create diverse interprofessional student teams that can explore and learn about the roles and responsibilities of other team members while they work on the development and practice of effective communication with each other and their community participants. This method of promoting IPE is consistent with Ezzendine and Price, who found that forming student teams, facilitating student introductions, and facilitating team dynamics were valuable [ 15 ].…”
Section: Methodssupporting
confidence: 77%
“…However, there is a lack of comprehensive evidence regarding IPE facilitation. Although there is literature analyzing the IPE facilitation process through qualitative research [11], there are no IPE facilitation programs developed through research to date. This study aimed to develop an IPE facilitation program for healthcare professionals to learn IPE facilitation skills, promote interprofessional collaboration in the participants' own organizations through research, and determine whether the facilitation skills of participating professionals could be enhanced and sustained.…”
Section: Introductionmentioning
confidence: 99%